Bladder cancer : risk factors, emerging treatment strategies and challenges - Haggerty, Samantha; Nova Biomedical (Publishing company). (New York : Nova Biomedical, 2014)
Bladder cancer is the fifth most common form of cancer worldwide and is mainly prevalent in developed countries. It is thought to arise through two distinct pathways: the noninvasive and the invasive. The noninvasive pathway gives rise to a superficial papillary carcinoma that is characterized by activating mutations in oncogenes such as H-ras, FGFR3 and PI3K. This pathway is rarely lethal as superficial papillary carcinomas can be readily removed through transurethral resection. However, 15% of noninvasive urothelial tumors can transform into invasive carcinomas and have high recurrence 80%.--
Cancer stem cell (CSC) in bladder malignancy / Jianmin Zhang (and two others) -- The five senses in bladder cancer diagnostics / Caterina Gulia (and four others) -- Bladder cancer in pediatric patients / Santiago Vallasciani (and four others) -- Multi-tasking chemoinformatic model for the efficient discovery of potent and safer anti-bladder cancer agents / Alejandro Speck-Planche and M. N. D. S. Cordeiro -- Long non coding mitochondrial RNAs as potential targets for diagnosis and therapy of bladder cancer / Jamie Villegas (and ten others) -- Histological variants of urothelial carcinoma / Hyung Suk Kin and Ja Hyeon Ku -- Novel therapeutic modalities in patients with advanced or metastatic urothelial carcinoma / Kazumasa Matsumoto (and four others).
Includes bibliographical references and index.
Keywords: Urinary Bladder Neoplasms